Das maneiras de negociar a realidade e expressar a fé: modelos devocionais e agenciamentos na festa e romaria ao Santuário de N. Sra. do Caravaggio - Silva, Adimilson Renato da (Universidade do Vale do Rio dos Sinos, 2015)
This work presents the research trajectory held in the empirical context of the pilgrimage and the shrine of Nossa Senhora do Caravaggio in the city of Farroupilha-RS. In order to build data, we made use of the ethnographic method, conducting participant observation, interviews, surveys on web sites, talks to the actors, filmic and photographic images of pilgrimages and periods Day Party May 26th. We seek to understand thereby as agencies of different actors influence the devotional gifts designs in devotion to Caravaggio. A demand for printing a "instrumental" logic to religion refers to the fact that culture goes through a process of profound reframing, changing its contours to the centrality that the performativity assumes nowadays in action and agents of the projects. Instead of privileging a single line of force or this action logic in the production and promotion of pilgrimage and other activities such as hiking, revitalization of sacred spaces, disclosure of devotion, etc., we decided to compose a panorama of perceptions from the insertion we had in the search field. This enabled voice and time to the action of the actors and their actions (SCHUTZ, 1974). A possible consideration is that although the agencies around the devotion to Caravaggio are converging to a common point, channel the potential to attract the faithful and pilgrims throughout the year, they remain still restricted to certain originality of vocalization interests, common goals and purposes. The movement to approach the sacred and religion is always tense and conflictive for individuals marked by urban sociability impacted by secularization and religious modernity. Although that rumored event, a church project becomes manifest in the midst of this period of religious deinstitutionalization.
Keywords: Agenciamentos; Projetos; Ressignificação; Devoção a Caravaggio; Agencies; Projects; Reframing; Devotion to Caravaggio; ACCNPQ::Ciências Humanas::Sociologia